Pertumbuhan, Produksi, dan Kualitas Buah Melon dengan Pemberian Pupuk Silika - Triadiati Triadiati; Mafrikhul Muttaqin; Nelly Saidah Amalia (Jurnal Ilmu Pertanian Indonesia, 2019)
Melon (Cucumis melo L.) is a plant that has economic value and has been cultivated in several areas of Indonesia with intensive fertilization. The mineral nutrient that is expected to improve the quality of melon growth and fruit is silica. The aim of the research was to improve the growth and melon fruit quality by addition of silica fertilizer. The treatments in this experiment were the application of silica (Novelgro, water soluble) which was carried out on melon plants with silica concentrations of 0.67; 1.33 ppm; and control (without silica). The results showed that silica increased the plant height, leaf area, and diameter of melon fruit. Melon plant with silica treatment of 1.33 ppm had silica content in the high category (>4% Si) which was 5.31% in the skin of the fruit. Moreover, the addition of silica can prolong the fruit storage period in room temperature compared to control.